Technologie informatyczne wspomagające strategię efektywnej obsługi klienta w łańcuchu dostaw - Łopaciński, Karol (Information Technologies Supporting the Efficient Consumer Response Strategy in the Supply Chain, 2007)
The ECR ("Efficient Consumer Response") movement effectively began in the mid-nineties and was characterised by the emergence of new principles of collaborative management along the supply chain. It was understood that companies can serve consumers better, faster and at less cost by working together with trading partners. Cooperation of the participants of the supply chain according to the ECR concept is based on the mutual communication and permanent flow of actual and complete information. It is possible because all cooperating firms use modern IT solutions such as: AI (Automatic Identification), EDI (Electronic Data Interchange) or EFT (Electronic Funds Transfer).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (10); 2007; nr 1150, s. 128-137